Evidence for a genetic contribution to the ossification of spinal ligaments in Ossification of Posterior Longitudinal Ligament and Diffuse idiopathic skeletal hyperostosis: A narrative review - Couto, Ana Rita; Parreira, Bruna; Power, Deborah M.; Pinheiro, Luís; Madruga Dias, João; Novofastovski, Irina; Eshed, Iris; Sarzi-Puttini, Piercarlo; Pappone, Nicola; Atzeni, Fabiola; Verlaan, Jorrit-Jan; Kuperus, Jonneke; et al. (Frontiers in Genetics, 2022)
Diffuse Idiopathic Skeletal Hyperostosis (DISH) and Ossification of the Posterior Longitudinal Ligament (OPLL) are common disorders characterized by the ossification of spinal ligaments. The cause for this ossification is currently unknown but a genetic contribution has been hypothesized. Over the last decade, many studies on the genetics of ectopic calcification disorders have been performed, mainly on OPLL. Most of these studies were based on linkage analysis and case control association studies. Animal models have provided some clues but so far, the involvement of the identified genes has not been confirmed in human cases. In the last few years, many common variants in several genes have been associated with OPLL. However, these associations have not been at definitive levels of significance and evidence of functional significance is generally modest. The current evidence suggests a multifactorial aetiopathogenesis for DISH and OPLL with a subset of cases showing a stronger genetic component.